'Culture-free' religion: new second-generation Muslims and Christians. Issue 1 (2nd January 2021) - Kurien, Prema A.
ABSTRACT: The turn to 'pure' Islam cleansed of the cultures of their parents' homeland traditions by children of Muslim immigrants in Europe and North America has been widely discussed. Scholars have attributed this behavior to factors particular to younger Muslims in the contemporary period or to the nature of Islam itself. In this article, I challenge these arguments by drawing on research on children of Christian immigrants in the United States who support a 'culture-free' Christianity, in contrast to the 'cultural' Christianity of their parents, and turn to American non-denominational evangelicalism. By making this comparison, my goal is to show that the decoupling of religion and ethnicity by children of immigrants is a broader phenomenon, not just confined to Muslims. I argue that it is a consequence of larger shifts in the understanding and practice of religion and ethnicity as well as assimilative pressures, racialization, and intergenerational dynamics. The comparison also demonstrates that the religious traditions embraced by the children of immigrants are not truly 'culture-free', but involve shedding ethnic languages and worship cultures to adopt dominant modes of religiosity.